Empowering behavior of the nurse-leader from the perspective of nursing technicians and assistants - da Graça, Elinalva Priscila Soares [UNESP]; de Oliveira, Priscila Braga [UNESP]; Spiri, Wilza Carla [UNESP] (Acta Paulista de Enfermagem, 2024)
Objective: Associate demographic and work data and the empowering behavior of the nurse-leader from the perspective of nursing technicians and assistants. Methods: Cross-sectional and correlational research carried out in a tertiary university hospital in the state of São Paulo. A total of 260 mid-level nursing professionals (nursing technicians and assistants) participated, using self-administered instruments from May to August 2021. To verify the association between the scale classes and the explanatory variables, a chi-square or Fisher’s exact test was performed in the SAS program. Relationships were statistically significant if p<0.05. Results: The profile of the participants was predominantly female, mean age 41.9 years, daytime workers, workload of 36.7 hours and satisfied with their work. The application of the Leader’s Empowering Behavior instrument showed that the domain with the highest average of empowering behavior was “meaningful work” and the one with the lowest average was “autonomy in relation to bureaucracy”. Nursing assistants and technicians who worked during the day did not have other work relationships and were satisfied with it, in addition to observing the leader’s empowering behavior more. Conclusion: Nurses’ behavior to empower their team, from the perspective of technicians and nursing assistants in the studied hospital, was good in most domains, except in the domain “autonomy from bureaucracy”, where it was reasonable. Working the day shift, not having other jobs and being satisfied with the job were aspects of greater empowerment.
Comportamiento empoderador de enfermeros líderes bajo la perspectiva de técnicos y auxiliares de enfermería
Comportamento empoderador do enfermeiro-líder na perspectiva de técnicos e auxiliares de enfermagem
Keywords: Empowerment; Leadership; Nurse administrators; Nursing, team; Practice management